Revitalizing (Ain Tawargha): Integrating landscape Architecture for Cultural Heritage Preservation and Sustainable Development (The International Journal of Engineering & Information Technology (IJEIT), 2025)
This research focuses on the revitalization of Ain Tawargha through landscape architecture, aiming to integrate cultural heritage preservation with sustainable urban development. Ain Tawargha, renowned for its natural springs and traditional handicrafts like (Dees) mats, faces challenges including urban decay and neglect of cultural assets. Employing a comprehensive approach, the study conducts site analysis, reviews previous studies, and gathers empirical data through surveys to propose practical interventions. Recommendations emphasize enhancing public spaces, promoting eco-friendly tourism, and revitalizing local crafts to stimulate economic growth and community engagement. By synergizing landscape design with cultural preservation, this research advocates for a balanced approach that respects local identity while fostering environmental sustainability and economic prosperity in Ain Tawargha.